"We Have Seen Other Countries and Have Another Culture." Migrant Domestic Workers and The International Production and Circulation of Feminist Knowledge and Organization. Issue 1 (March 2016) - Federici, Silvia
Abstract : This article argues that a movement of domestic workers has developed internationally that through its struggles is promoting elements of a feminist agenda, revalorizing the work of reproduction, forcing a new generation of feminists to again confront the housework question, and in this process generating new forms of subjectivities and new models of gender relations.